TINJAUAN YURIDIS PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA - Puanandini, Dewi Asri; Rismawati, Neng; Putri, Devia Noviani Sundari (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2024)
Corruption in Indonesia has become a chronic problem in the country's legal system, where this act has existed for a long time and occurs in various countries, both developed and developing, including Indonesia. Over time, corruption in Indonesia has become more complex and systemic, penetrating all levels of society. Initially, the crime of corruption was regulated in the Criminal Code. However, the development of society encourages legal changes to be more specific through the application of the lex specialis principle, which is further regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption. This research offers novelty in the form of an in-depth analysis of the effectiveness of lex specialis implementation in the eradication of corruption, especially in the context of handling high-ranking officials elected through political parties. In addition, this study reveals how the obligation to return state losses as a criminal sanction in the GCPL Law acts not only as a form of economic responsibility, but also as a social instrument to build public trust in the legal system. This study is expected to contribute to the strengthening of legal policies that are more effective in preventing and eradicating corruption in Indonesia. In practice, corruption is often committed by high-ranking officials who are generally elected through political parties. Under the GCPL Law, corruptors are required to compensate the state as a form of responsibility for the economic and social impacts caused. Increasing criminal penalties for perpetrators of corruption aims to provide a deterrent effect and is expected to reduce the number of corruptions in Indonesia.ABSTRAKKorupsi di Indonesia telah menjadi masalah kronis dalam sistem hukum negara, di mana tindakan ini telah ada sejak lama dan terjadi di berbagai negara, baik yang maju maupun berkembang, termasuk Indonesia. Seiring perkembangan waktu, korupsi di Indonesia menjadi lebih kompleks dan sistemik, menembus seluruh lapisan masyarakat. Awalnya, tindak pidana korupsi diatur dalam Kitab Undang-Undang Hukum Pidana. Namun, perkembangan masyarakat mendorong perubahan hukum menjadi lebih spesifik melalui penerapan prinsip lex specialis, yang diatur lebih lanjut dalam Undang-Undang Nomor 31 Tahun 1999 juncto Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Penelitian ini menawarkan novelty berupa analisis mendalam terhadap efektivitas implementasi lex specialis dalam pemberantasan korupsi, khususnya dalam konteks penanganan pejabat tinggi yang terpilih melalui partai politik. Selain itu, penelitian ini mengungkapkan bagaimana kewajiban pengembalian kerugian negara sebagai sanksi pidana dalam UU PTPK berperan tidak hanya sebagai bentuk tanggung jawab ekonomi, tetapi juga sebagai instrumen sosial untuk membangun kepercayaan publik terhadap sistem hukum. Kajian ini diharapkan dapat memberikan kontribusi terhadap penguatan kebijakan hukum yang lebih efektif dalam mencegah dan memberantas korupsi di Indonesia. Pada praktiknya, korupsi sering dilakukan oleh pejabat tinggi yang umumnya terpilih melalui partai politik. Berdasarkan UU PTPK, koruptor diwajibkan mengganti kerugian negara sebagai bentuk tanggung jawab atas dampak ekonomi dan sosial yang ditimbulkan. Peningkatan hukuman pidana bagi pelaku korupsi bertujuan memberikan efek jera dan diharapkan mampu menekan angka korupsi di Indonesia.